2012
DOI: 10.1111/j.1574-6941.2012.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes and pathogenicity islands in environmentalVibriostrains nonpathogenic to humans

Abstract: Most Vibrio species in autochthonous marine microbial communities, such as Vibrio alginolyticus, Vibrio harveyi, Vibrio anguillarum among others, are considered nonpathogenic for humans. However, because many bacterial virulence genes are located in mobile genetic elements, the acquisition of mobile DNA could mediate the appearance of virulent or more virulent strains even in a species defined as nonpathogenic. In this study, we screened a collection of marine nonpathogenic Vibrio strains isolated in the area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 38 publications
0
49
0
2
Order By: Relevance
“…Many of the algal exudate-enriched OTUs identified here by 16S amplicon sequencing were related to cultured isolates identified as known pathogens, but closely related species and strains within bacterial generic-level clades can exhibit very different hostpathogen dynamics depending on conditions or how cellular machinery is used (Coenye and Vandamme, 2003;Jani and Cotter, 2010;Gennari et al, 2012). The evidence presented here should be interpreted as hypothesis-generating rather than definitive proof that algal exudates select for coral pathogens.…”
Section: Ecological Implicationsmentioning
confidence: 68%
“…Many of the algal exudate-enriched OTUs identified here by 16S amplicon sequencing were related to cultured isolates identified as known pathogens, but closely related species and strains within bacterial generic-level clades can exhibit very different hostpathogen dynamics depending on conditions or how cellular machinery is used (Coenye and Vandamme, 2003;Jani and Cotter, 2010;Gennari et al, 2012). The evidence presented here should be interpreted as hypothesis-generating rather than definitive proof that algal exudates select for coral pathogens.…”
Section: Ecological Implicationsmentioning
confidence: 68%
“…Among these, V. anguillarum behaves as a major pathogen for a variety of aquatic organisms (fishes, eels, crustaceans, marine mammals, and corals). Although the environmental isolates are usually lacking the virulence-associated genes found in the clinical ones, some recent studies showed that they can also carry such genes, or homologues thereof, acquired through horizontal transfer events (Kirkup et al 2010;Gennari et al 2012). Both the persistence and abundance of vibrios are related to several parameters, whose influence can differ according to the geographic region .…”
Section: Introductionmentioning
confidence: 98%
“…Sporadic reports of V. parahaemolyticus-like virulence genes in other species have appeared in the literature (33)(34)(35)(36)(37)(38)(39), but little is known regarding the distributions of these genes among Vibrionaceae. In particular, the occurrence of these genes in environmental strains has received very little attention.…”
mentioning
confidence: 99%